β-hydroxybutyrate impairs monocyte function via the ROS-NLR family pyrin domain-containing three inflammasome (NLRP3) pathway in ketotic cows - Dong, Zhihao; Sun, Xudong; Tang, Yan; Luo, Shengbin; Jia, Hongdou; Xu, Qiushi; Jiang, Qianming; Loor, Juan J.; Xu, Wei; Xu, Chuang (Frontiers in Veterinary Science, 2022)
Cows with ketosis display severe metabolic stress and immune dysfunction which renders them more susceptible to infections. Monocytes, one of the major subtypes of white blood cells, play an important role in innate immune defense against infections. Thus, the aim of this study was to investigate alterations in immune function, reactive oxygen species (ROS) production and activity of the NLR family pyrin domain containing 3 (NLRP3) inflammasome pathway in monocytes (CD14+) of cows with clinical ketosis (CK). Twelve healthy multiparous Holstein cows (blood β-hydroxybutyrate [BHB] concentration < 1.2 mM) and 12 cows with CK (BHB > 3.0 mM) at 3 to 14 days in milk were used for blood sample collection. To determine effects of BHB on phagocytosis, ROS and protein abundance of the NLRP3 inflammasome pathway in vitro, monocytes isolated from healthy cows were treated with 3.0 mM BHB for 0, 6, 12 or 24 h. Dry matter intake (22.7 vs. 19.0 kg) was lower in cows with CK. Serum concentrations of fatty acids (0.30 vs. 0.88 mM) and BHB (0.52 vs. 3.78 mM) were greater in cows with CK, whereas concentration of glucose was lower (4.09 vs. 2.23 mM). The adhesion, migration and phagocytosis of monocytes was lower in cows with CK, but apoptosis and ROS content were greater. Protein abundance of NLRP3, cysteinyl aspartate specific proteinase 1 (caspase 1) and interleukin-1B p17 (IL1B p17) was greater in monocytes of cows with CK, while abundance of NADPH oxidase isoform 2 (NOX2) was lower. Compared with treated 3.0 mM BHB for 0 h, ROS content and apoptosis, and the protein abundance of NLRP3, caspase 1, and IL1B p17, and concentration of IL1B in medium were greater in the monocytes challenged for 6, 12 or 24 h with BHB. However, protein abundance of NOX2 and phagocytosis of monocytes were lower. Overall, the data suggested that exogenous BHB activated the ROS-NLRP3 pathway, which might be partly responsible for immune dysfunction of dairy cows with CK.